PENGARUH TOTAL REWARD TERHADAP JOB ENGAGEMENT SERTA DAMPAKNYA TERHADAP KINERJA PEGAWAI - Chresno Wahyu Widodo (MIX: JURNAL ILMIAH MANAJEMEN, 2014)
Abstract: Total Reward combines Transactional Reward and Relational Reward can meet any level of employee‘s needs therefore will foster employee to invest their Job involvement (cognitive energy), Job satisfaction (emotional reaction), Intrinsic motivation (physical energy) actively into complete work role performance. If employee shows Job Engagement during work in turn will create superior performance that are directly involved in the accomplishment of core job tasks involved in organization‘s =technical core‘ (task performance) and also motivational behavior such cooperation, helpfulness, innovation, contribute to organization by fostering a social and psychological environment conducive to accomplishment of work involved in organization‘s =technical core‘ (contextual performance). Result of the study taken by questionnaire to employee of Sekretariat Pengadilan Pajak confirm our hypothesesrelationships between Total Reward and Job Engagement also relationships between Job Engagement and Job Performance. In fact our results support our hypotheses that mediating role of Job Engagement accounts for relationships between Total Reward and Job Performance.Keywords: Total Reward, Job Engagement, Job Performance, Mediating Role of Job Engagement